Novas espécies de Virola Aubl. (Myristicaceae) da Amazônia - Rodrigues, William Antônio (Acta Amazonica, 1977)
In this paper five miristicaceous species from Brazilian Amazonia are described and illustrated as new ones: Virola caducifolia, V. coelhoi, V. guggenheimii, V. marlenei and V. polyneura.